Dilemma of HCV Infection in Renal Transplant Recipients - Osama Ashry Ahmed Gheith (International Journal of Nephrology)
Hepatitis C virus, which usually starts during dialysis therapy, is currently the main cause of chronic liver disease in such population. The majority of patients acquired the disease through intravenous drug use or blood transfusion, with some risk factors identified. In this review we are dealing with the effect of renal transplantation on HCV infection and HCV-related complications after renal transplantation. Moreover, we are discussing the therapeutic options of HCV infection before and after renal transplantation, the best immunosuppressive protocol and lastly graft and patient survival in patients who underwent pretransplant management vs. those who were transplanted without treatment.